Dynasties, Legacies, and Strategies of Heritage Preservation: Elite Patrimonial Practices in Colonial La Rioja (17th–Early 18th Century) - Jorge Hugo Villafañe (Histories, 2025)
During the 17th and early 18th centuries, within the framework of Castilian inheritance law—which mandated the equal partition of marital assets among all legitimate descendants—the elites of colonial La Rioja devised a set of complex and adaptive strategies to safeguard the integrity of their principal estates. This study examines four lineages spanning three to six generations to analyze the mechanisms employed to ensure patrimonial continuity. These included the foundation of mayorazgos (entailments), strategic transactions among co-heirs, differentiated inheritance arrangements, the symbolic and legal assignment of familial roles, and highly endogamous marriage patterns. In a region characterized by demographic constraints, limited commercial integration, and economic stagnation, elite families also relied on credit networks involving landowners, convents, and merchants to sustain their influence. By situating these practices within broader colonial legal frameworks and recent historiography on legal pluralism and credit economies, this article offers a nuanced understanding of the legal, social, and financial instruments that shaped elite reproduction in a peripheral colonial setting.